Preliminary design study of a simple neutron energy spectrometer using a CsI self-activation method for daily QA of accelerator-based BNCT. Issue 1 (2nd January 2019) - Kurihara, Ryosuke; Nohtomi, Akihiro; Wakabayashi, Genichiro; Sakurai, Yoshinori; Tanaka, Hiroki
ABSTRACT: For recent boron neutron capture therapy (BNCT), accelerator-based neutron sources have been actively developed in place of reactor-based neutron sources. In this study, a novel neutron energy spectrometer for the daily quality assurance (QA) of BNCT was designed on the basis of a CsI self-activation method for accelerator-based neutron sources. The spectrometer design was optimized in terms of its energy resolution. To verify its applicability to high-intensity BNCT neutron fields, some practical simulations were performed. It was shown that the designed spectrometer was able to evaluate a neutron energy spectrum in approximately 900 s after an instantaneous neutron irradiation. In addition, its energy resolution was sufficient for detecting an unexpected distortion in the spectrum. The results confirm that the designed spectrometer can be employed for the daily QA of BNCT to check that the expected spectrum remains unchanged.